Making music together: an exploration of amateur and pro-am Grime music production - McGrath, Sean; Chamberlain, Alan; Benford, Steve (2016)
This novel research presents the results of an ethnographic study, which focused upon the production of an EP created by an amateur and a pro-amateur producer. The research presents their production practices across the production workflow, from inception and ideation through to completion. The paper describes the distinct processes that occur when collaborating on the production of the EP. The exploration here discusses the use of software systems to facilitate production of a series of music tracks. We further explicate the use of technologies in the production settings, and these range from mobile devices (smartphones) through to digital audio workstations. Further to this, we start to map out how the technology used affords and supports collaboration and communication across a distributed context. We respond to our findings by presenting a series of design implications that address the research.